2014
DOI: 10.1016/j.matdes.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tool geometry and rotational speed on mechanical properties and defect formation in friction stir lap welded 5456 aluminum alloy sheets

Abstract: Friction stir welding of AA5456 aluminum alloy in lap joint configuration is with two different tempers, T321 and O, and different thicknesses, 5mm and 2.5mm was investigated. The influences of tool geometry and various rotational speeds on macrostructure, microstructure and joint strength are presented. Specifically, four different tool pin profiles (a conical thread pin, a cylindrical-conical thread pin, a stepped conical thread pin and Flared Triflute pin tool) and two rotational speeds, 600 and 800 rpm, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(51 citation statements)
references
References 19 publications
3
41
0
Order By: Relevance
“…Of special interest is also the work of Fujii et al [12] on the effect of tool geometry on mechanical and microstructural properties of friction stir welded 1050-H24, 6061-T6, and 5083-O aluminum plates. Recently, the present authors [18] showed that a stepped conical threaded pin gives more homogeneous and defect free joints.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Of special interest is also the work of Fujii et al [12] on the effect of tool geometry on mechanical and microstructural properties of friction stir welded 1050-H24, 6061-T6, and 5083-O aluminum plates. Recently, the present authors [18] showed that a stepped conical threaded pin gives more homogeneous and defect free joints.…”
Section: Introductionmentioning
confidence: 70%
“…Indeed, during FSW lap welding, the material of the lower plate is pushed up toward the upper one [19]. amount of plastic deformation and centrifugal forces than the one in the lower plate [18]. As a result, the stir zone in the upper plate has a more uniform structure and consequently similar hardness.…”
Section: Microhardness Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is clear from the macrographs that obvious defects are observed in the samples at most process parameters. Actually, FSLW was developed based on the principle of FSW, and FSW has been widely found to have the characteristic of narrow parameter range [16][17][18][19][20]. For the current case, it is more difficult to produce high-quality welds by FLSW compared with the widely studied friction stir butt welding.…”
Section: Single-track Friction Stir Lap Weldingmentioning
confidence: 99%